Mycorrhiza increases plant diversity and soil carbon storage in grasslands - Entao Zhang; Yang Wang; Thomas W. Crowther; Weicheng Sun; Shiping Chen; Daowei Zhou; Zhouping Shangguan; Jianhui Huang; Jin-Sheng He; Yanfen Wang; Jiandong Sheng; Lisong Tang; et al. (Proceedings of the National Academy of Sciences, 2025)
Experimental studies have shown that symbiotic relationships between arbuscular mycorrhizal (AM) fungi and host plants can regulate soil organic carbon (SOC) storage. Although the impacts of mycorrhiza are highly context-dependent, it remains unclear how these effects vary across broad spatial scales. Based on data from 2296 field sites across grassland ecosystems of China, here we show that mycorrhizal fungi symbiosis enhances SOC storage in the topsoil and subsoil through increasing plant diversity and elevating biomass allocation to belowground. SOC storage is significantly higher in both the topsoil and subsoil in systems dominated by obligate mycorrhizal (OM) and facultative mycorrhizal (FM) plants than those dominated by nonmycorrhizal (NM) plants. Also, the relative abundance of OM plants increases at the expense of FM plants as temperature and precipitation increase. These findings provide valuable insights into the potential mechanisms by which mycorrhizal fungi may influence grassland plant diversity and SOC storage in the context of global change.